CACNA1C, schizophrenia and major depressive disorder in the Han Chinese population. (January 2014) - He, Kuanjun; An, Zhiguo; Wang, Qingzhong; Li, Tao; Li, Zhiqiang; Chen, Jianhua; Li, Wenjin; Wang, Ti; Ji, Jue; Feng, Guoyin; Lin, He; Yi, Qizhong; et al.
Abstract : Background: Common psychiatric disorders are highly heritable, indicating that genetic factors play an important role in their aetiology. The CACNA1C gene, which codes for subunit alpha-1C of the Cav1.2 voltage-dependent L-type calcium channel, has been consistently found to be the shared risk gene for several kinds of mental disorder. Aims: To investigate whether CACNA1C is a susceptibility gene for schizophrenia and major depressive disorder in the Han Chinese population. Method: We carried out a case–control study of 1235 patients with schizophrenia, 1045 with major depressive disorder and 1235 healthy controls. A tag single nucleotide polymorphism (SNP) rs1006737 along with another 10 tag SNPs in the CACNA1C gene were genotyped in all samples. Results: We found that rs1006737 was associated with both schizophrenia ( P allele = 0.0014, P genotype = 0.006, odds ratio (OR) = 1.384, 95% CI 1.134–1.690) and major depressive disorder ( P allele = 0.0007, P genotype = 0.003, OR = 1.425, 95% CI 1.160–1.752). Conclusions: Our findings support CACNA1C being a risk gene for both schizophrenia and major depressive disorder in the Han Chinese population.